Maria Luisa, by Lucia Miguel Pereira: The meeting of the Social and Subjective Crisis by the Displacement in the Religious Discourse - Coelho, Elisa Domingues [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2019)
Maria Luisa, by Lucia Miguel Pereira, diverges from the literary context of the 1930's by bringing a female character as the organizing axis of the novel, which enables her look to pass through all the characters and determine what one should think of them. In the literary project of the novel, this view of the protagonist will move through a spiral process of rememoration and re-signification, contrasting with an unquestionably simple plot, reflecting the stratified social and moral structures. Thus, Maria Luisa re-signifies her former place and begins to live in the abyss, a transit that makes the place of the characters of the 1930s impossible, as they are neither able to bond to the decadent past, nor find themselves in the future that modernity brings.
Keywords: 1930's; Brazilian Literature; Lucia Miguel Pereira; Maria Luisa; Modernism; Novel